2013
DOI: 10.1253/circj.cj-13-0387
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Implantable Cardioverter Defibrillator Home Monitoring in Forecasting the Need for Regular Office Visits, and Patient Perspective

Abstract: RM-based forecasts appear sufficiently accurate to safely individualize RFU. Most patients have a positive attitude towards RM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Besides these large registries, some smaller (prospective) observational studies included measures of health status, satisfaction and/or acceptation, RPM experiences, and preferences for follow‐up . The majority used self‐designed questionnaires . Only one observational study of remotely monitored patients (N = 124) assessed health status, and found stable scores on the 36‐item Short Form Health Survey (SF‐36) during the first 6 months after implantation and high satisfaction with RPM using a purpose‐designed questionnaire .…”
Section: Nonrandomized Studies On the Patient Perspective On Rpmmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these large registries, some smaller (prospective) observational studies included measures of health status, satisfaction and/or acceptation, RPM experiences, and preferences for follow‐up . The majority used self‐designed questionnaires . Only one observational study of remotely monitored patients (N = 124) assessed health status, and found stable scores on the 36‐item Short Form Health Survey (SF‐36) during the first 6 months after implantation and high satisfaction with RPM using a purpose‐designed questionnaire .…”
Section: Nonrandomized Studies On the Patient Perspective On Rpmmentioning
confidence: 99%
“…In an Italian study (N = 119), 90% of patients reported that RPM did not influence daily activities and 95% reported that RPM did not bother them . A Japanese study (N = 215) showed that 93% found RPM not bothersome . Few studies reported on patient preferences, indicating that 78–98% of patients expressed a preference for RPM and wished to continue RPM after study participation .…”
Section: Nonrandomized Studies On the Patient Perspective On Rpmmentioning
confidence: 99%
“…A qualification system may also be needed for expert nurses who are specialized in remote monitoring of implanted devices. 10 Finally, although the vast majority of patients had a positive attitude and experience with Home Monitoring in this study, 4 the fact remains that a minority of patients, mostly elderly patients, do not accept it, primarily because of fear of technology or concerns about the risk of losing contact with doctors or hospitals. 12 Simpler devices/systems or novel operational platforms device event and the time scheduled for the next regular inhospital follow-up visit.…”
Section: Article P 2704mentioning
confidence: 77%
“…4 The primary objective was to evaluate the reliability of Home Monitoring technology in predicting the need for regular in-hospital followups (3, 6, 9, or 12-months' follow-up). To this end, the pre-and post-follow-up assessments for regular visits were compared to derive the rate of true and false predictions.…”
Section: Article P 2704mentioning
confidence: 99%
“…So far, clinical evidence from Japan supporting the efficacy of the RM technology has been limited. The HOME‐ICD study reported by Watanabe et al [18] evaluated the reliability of daily wireless RM in forecasting the need for regular in‐hospital follow‐ups (RFUs). Two‐hundred fifteen patients implanted with ICDs or CRT‐Ds were enrolled, and RFUs were performed at 3, 6, 9, and 12 months after implantation.…”
Section: Emerging Clinical Evidence For Rmmentioning
confidence: 99%